OPTIMASI PEMBUATAN MEMBRAN KERAMIK BERBAHAN DASAR LEMPUNG BOJONEGORO DAN LIMBAH INDUSTRI KERAJINAN KERAMIK DENGAN PENAMBAHAN BATUBARA SEBAGAI ZAT ADDITIVE - , WIRA WIDYAWIDURA, Indra Perdana, S.T., M.T., Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Has been held the research about Optimization of ceramic membrane for water filtration from Bojonegoro Clay and ruins waste of ceramic craft industry (grog) with coal adding as additive/combustible material. The coal added variation including 0%, 5%, 10%, 15%, 25%, 30% from clay mass. They are produced by dry pressing method with 17,45 MPa of molding pressure on raw materials and fired at 870 oC with 2 oC/minute of heat rate and 15 minute of holding time temperature. Filtration process has been done on ceramic membrane apparatus with -50 cmHg of vacuum pressure (pressure drop = 68131,18) NS 65,35 NTU of average of artificial turbidity. The result show that the most optimum ceramic membrane sample for turbidity removal is the sample with 15 % of coal adding (250 gr clay, 25 gr grog, and 37,5 gr coal) that have the % turbidity removal value are 96,46%